The Effect of Heat-treated Poultry Pellets and Composted Poultry Litter on E. coli Survival in Southeastern US Soils: Florida and Georgia - Karuna Kharel; Cameron A. Bardsley; Charles Bency Appolon; Laurel L. Dunn; Govindaraj Dev Kumar; Krishna Prabha; Manan Sharma; Michelle D. Danyluk; Keith R. Schneider (Journal of Food Protection)
Biological soil amendments of animal origin (BSAAO) are a source of foodborne pathogens that can contaminate fresh produce. This study evaluated the survival of E. coli over 140 d in agricultural soils amended with composted poultry litter (PL), heat-treated poultry pellets (HTPP), or unamended (UN) in Florida (FL) and Georgia (GA). Raised-bed plots (1 × 3 m2; n = 3) were either left unamended (UN) or amended with PL or HTPP (680 g/plot). Each plot was spray-inoculated with 1 L of rifampicin-resistant E. coli (7–8 log CFU/mL) and hand-tilled into the soil (∼5.9 and 4.5 log CFU/g for FL and GA, respectively). Soil samples were enumerated using a spread plate or most probable number technique at 0, 1, 3, 7, 14, 28, 56, 84, 112, and 140 d. Weather-related parameters were collected to assess their impact on E. coli survival. A mixed-model analysis was used to evaluate factors influencing E. coli survival, a biphasic model was used for the E. coli die-off rate, and Spearman correlations were used to understand the associations between environmental factors and survival. Time, amendment type, and location * treatment * time influenced (P < 0.05) the survival of E. coli in soil. In FL, HTPP-amended soils supported higher levels of E. coli compared to PL-amended soils; in Georgia, similar survival was observed between PL- and HTPP-amended soils, both of which were higher (P < 0.05) than in UN soils. In both locations, E. coli levels fell to the limit of detection (−0.24 log MPN/g) by 112 d in UN plots; however, they persisted at levels between 0.30 and 1.57 log CFU/g in HTTP- and PL-amended soils until 140 d. Weak to moderate correlations were observed for rainfall and soil moisture and their effect on E. coli survival; no other weather factors were impactful. The use of BSAAO in soils can prolong the survival of E. coli (>140 d) irrespective of the factors intrinsic to the locations and have implications regarding the safe use of BSAAOs during fruit and vegetable production.